Resource Dependence Dynamics: Partner Reactions to Mergers - Rogan, Michelle; Greve, Henrich R. (Organization Science, 2015)
Research on resource dependence typically takes a static view in which actions and outcomes are determined structurally, but not as responses to the actions of the counterparty in an exchange relation. By contrast, this study addresses a question of power dynamics by examining whether mergers of organizations trigger responses from their common exchange partners. We predict that common exchange partners respond by withdrawing from the relationship and that their responses vary with the availability of alternatives, the value of the relationship, and the relationship history. Using data on advertising agencies, we show that mergers of agencies do trigger reactions from their common clients, and the reactions differ with agency and client characteristics. Extending existing theory and evidence, our results suggest that firms respond to the dynamics of exchange relationships and not only to their structure.